2018
DOI: 10.14710/humanika.v25i1.18128
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bumi Manusia Karya Pramoedya Ananta Toer Kajian Sosiologi Sastra

Abstract: Bumi Manusi is a novel showing the mental turmoil of the characters situated between two cultures, two values

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…The Hybridity of Indies Culture in Indonesian Novel Translation into French cultures and values (Hastuti, 2018;Nasution et al, 2020). However, this article found that Bumi Manusia depicts the other culture, Indies/Indische culture, between the two cultures.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The Hybridity of Indies Culture in Indonesian Novel Translation into French cultures and values (Hastuti, 2018;Nasution et al, 2020). However, this article found that Bumi Manusia depicts the other culture, Indies/Indische culture, between the two cultures.…”
Section: Discussionmentioning
confidence: 66%
“…The analysis found two main reasons for Indies culture's dominance in the social life category in BM. First, the story focuses on describing the Dutch East Indies community's life, especially the life of indigenous figures (Minke) in the midst of European and Indo-European groups who received education and experienced Western civilization (Hastuti, 2018;Murwani, 2013). Educated natives such as Minke are among the prominent supporters of Indies culture (Soekiman, 2011).…”
Section: Types Of Indies Culture Hybrid Elements In Bumi Manusiamentioning
confidence: 99%
See 1 more Smart Citation
“…Karya sastra merupakan bentuk hasil yang dilakukan seorang pekerja seni kreatif yang membuat bahasa sebagai media, dan manusia sebagai objek. Karya sastra dihadirkan sebagai wadah untuk menuangkan semua reaksi dan tanggapan dari penulis, peneliti dapat kebebasan berbicara atau berekspresi pendapatnya tentang kehidupan pengalaman pribadi atau orang lain dengan berbagai peraturan juga norma dalam hubungannya dengan lingkungan (Amu, 2019;Hastuti, 2018;Nugraha, 2019). Karya sastra menurut Swingewood (1972) adalah dokumen sosiobudaya yang dapat digunakan untuk melihat suatu fenomena dalam masyarakat pada masa tersebut.…”
Section: Pendahuluanunclassified
“…Novel Bumi Manusia (2002) mengangkat latar belakang sejarah pra-kemerdekaan Indonesia yang sarat akan nilai-nilai nasionalisme dan kolonialisme (Farhana & Aflahah, 2019), kelas sosial (Hastuti, 2018;Nisa, 2019), rasisme (Ridwan & Sofianto, 2019), dan emansipasi (Akbar, 2019;Rahayu, Muliawati, & Pujiatna, 2019). Kesemua nilai ini terealisasi tidak hanya melalui struktur wacana dan pelataran, tetapi juga melalui gaya kebahasaan Pramoedya di dalam novel.…”
Section: Pendahuluanunclassified